2012
DOI: 10.1007/s12263-012-0317-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide-related thiol metabolism and nutrigenetics in relation to hypertension in an elderly population

Abstract: Hydrogen sulphide (H 2 S) is a gaseous signalling molecule that regulates blood flow and pressure. It is synthesised from cysteine via cystathionine b-synthase and cystathionine c-lyase. We examined whether thiol precursors of H 2 S, transsulphuration pathway gene variants (CBS-844ins68 and CTH-G1364T) and key B-vitamin cofactors might be critical determinants of hypertension in an elderly Australian population. An elderly Australian retirement village population (n = 228; age 65-96 years, 91 males and 137 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“… 14 Our mean population homocysteine levels (10.4 μmol/L) are slightly higher than a New South Wales (NSW) Central Coast aged cohort (9.39 μmol/L), where a significant proportion of the participants were hypertensive. 16 Logistic models in the NSW Central Coast study did not reveal a significant interaction with blood pressure and homocysteine levels. 16 We found that a previous history of hypertension influenced QRS duration (the primary outcome measure) in our studies, although when modeled as an interactive factor in regression models (with age and gender), the association with homocysteine and QRS duration was reduced.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“… 14 Our mean population homocysteine levels (10.4 μmol/L) are slightly higher than a New South Wales (NSW) Central Coast aged cohort (9.39 μmol/L), where a significant proportion of the participants were hypertensive. 16 Logistic models in the NSW Central Coast study did not reveal a significant interaction with blood pressure and homocysteine levels. 16 We found that a previous history of hypertension influenced QRS duration (the primary outcome measure) in our studies, although when modeled as an interactive factor in regression models (with age and gender), the association with homocysteine and QRS duration was reduced.…”
Section: Discussionmentioning
confidence: 88%
“… 16 Logistic models in the NSW Central Coast study did not reveal a significant interaction with blood pressure and homocysteine levels. 16 We found that a previous history of hypertension influenced QRS duration (the primary outcome measure) in our studies, although when modeled as an interactive factor in regression models (with age and gender), the association with homocysteine and QRS duration was reduced. On the other hand, our subgroup consisted of only 21 participants with a QRS duration >120 ms, therefore we cautiously report our adjustments with respect to demographic clinical history in regression models and do not overstate their significance.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the true effect of CSE deficiency on BP remains unclear at present. Lucock et al found that both genetic variants of CSE-G1364T and CBS-844ins68 are biological determinants of H2S synthesis and are aetiologically important in the regulation of BP (Lucock et al, 2013). In addition, it has been observed that mean arterial pressure (MAP) in rats is not enhanced after treatment with either the CSE inhibitor DL-propargylglycine (PAG) or the CBS inhibitor aminooxyacetic acid (AOA) alone for 4 weeks; however, MAP increased gradually from 99 ± 2 to 130 ± 1 mmHg during 4 weeks of treatment with the combination of PAG and AOA (Roy et al, 2012).…”
Section: L-cysteine Xe991mentioning
confidence: 99%
“…The mutation causes CBS metabolic activity to decrease and affects the metabolism of Hcy. Previous studies have shown that the CBS844ins68 gene polymorphisms exist in different populations; the frequency of the insertion (I) allele was 10% in Britian, 7% in Pakistan and 1.4% in the Henan Han population (7)(8)(9). Thus far, the correlation of the CBS844ins68 gene polymorphism and EH is rarely reported in domestic and foreign countries.…”
Section: Introductionmentioning
confidence: 99%